Academia in the Northern Forest Lands Debate: Research Versus Chronic Brushfires - Field, David (Maine Policy Review, 1993)
David Field of the Department of Forest Management, University of Maine, offers his observations on the role of academia in the important debate over the future of the Northern Forestlands.